Hubungan Tingkat Pendidikan, Pekerjaan, Dan Pengetahuan Ibu Dengan Ketepatan Jadwal Mengikuti Imunisasi Campak Di Wilayah Kerja Puskesmas Weru Sukoharjo - Putra Destiyanta, Aditama; , Yuli Kusumawati, SKM., M. Kes (Epid); , Anisa Catur Wijayanti, SKM., M.Epid (2015)
Immunization was the vaccination effort to improve the baby's immune from the disease. Infants must obtain five basic immunization before one year. The vaccinations which was late can still functioned well although not provided by optimal protection. Measles immunization coverage in Weru is still low compared with other region in Sukoharjo that is 73,3%. The aims of this research was to determine the relationship between education, employment, and knowledge of mothers with accuracy following the measles immunization schedule. This study is a observational research with cross sectional study. The population was all mothers of children who have measles immunized from January until July 2014 in the Puskesmas Weru Region. Sampling technique was used proportional random sampling. Data analyses used Chi Square test by software computer. The result showed that there was no relation between a level of education of mothers with accuracy following the measles immunization schedule (p=0,403), there was no relation between employment of mothers with accuracy following the measles immunization schedule (p=0,166), there was no relation between knowledge of mothers with accuracy following the measles immunization schedule (p=0,122).